270 Cervical cancer and human papillomavirus awareness, vaccine status and risk factors among women in Saudi Arabia. (13th November 2020) - Akkour, K; ARAFAH, M; Alghosun, L; Alhalal, H; Bassi, A; Alayed, N; Iqbal, S
Abstract : Introduction: Cervical cancer (CC) is the 8th most common cancer among Saudi women of all ages. With limited national data, we aimed to evaluate the public awareness in regards to CC risk factors, HPV infection and HPV vaccines in the different regions of Saudi Arabia. Methods: This is a survey-based cross-sectional study that encompassed 564 Saudi women during a period of a month. A self-administrated questionnaire was distributed through different social media platforms. Data collected included socio-demographic variables and questions assessing the awareness of CC and the attitudes in regards to CC screening and HPV vaccine. Result: Most respondents were aware of CC (474, 84.0%) though their primary source of information was the internet. However, only 45 females (8%) gave a history of cervical screening. Furthermore, most females did not know that HPV is transmitted sexually (78.9%) or that it causes genital warts (81.7%) and CC (81.9%). In regards to the HPV vaccine, 100 females (17.7%) have heard about it but only 11 (2%) took the vaccine though more than half of the respondents (305, 54.1%) were willing to take the vaccine after being informed about it. Conclusion: There is a remarkably lack of awareness within the Saudi women regarding the HPV clinical implications, HPV vaccine, its importance and its availability. The main resource of information for most Saudi women is the internet which may be unreliable or providing misleading information that may delay screening or discourage vaccination. Thus, organized campaigns by the Ministry of Health or other health advocating agencies are strongly encouraged.